Novel Electronic Device to Quantify the Cyclic Fatigue Resistance of Endodontic Reciprocating Files after Using and Sterilization - Álvaro Zubizarreta-Macho; Óscar Alonso-Ezpeleta; Alberto Albaladejo Martínez; Vicente Faus Matoses; Javier Caviedes Brucheli; Rubén Agustín-Panadero; Jesús Mena Álvarez; Fernando Vizmanos Martínez-Berganza (Applied Sciences, 2020)
Background: The aim of this study was to analyze the effects of the time of use (TU) and sterilization cycles (SC) of endodontic reciprocating files on cyclic fatigue resistance. Methods: One-hundred-and-twenty (120) Procodile NiTi endodontic reciprocating instruments were selected at random and distributed into the following study groups: A: 0 sterilization cycles/0s time of use (n = 10); B: 0/60 (n = 10); C: 0/120 (n = 10); D: 1/0 (n = 10); E: 1/60 (n = 10); F: 1/120 (n = 10); G: 5/0 (n = 10); H: 5/60 (n = 10); I: 5/120 (n = 10); J: 10/0 (n = 10); K: 10/60 (n = 10); and L: 10/120 (n = 10). A dynamic cyclic fatigue device was designed using computer-aided design/computer-aided engineering (CAD/CAE) technology and created with a 3D printer to simulate the pecking motion performed by the clinician. Failure of the endodontic rotary instrument was detected by a light-emitting diode-light-dependent resistor (LED-LDR) system controlled by an Arduino driver complex and management software. The results were analyzed using the ANOVA test. Results: All pairwise comparisons presented statistically significant differences between the time to failure, number of cycles to failure and number of cycles of in-and-out movement for the time of use study groups (p < 0.001), but not in the number of sterilization cycles (p > 0.05). Conclusions: The time of use of NiTi endodontic reciprocating files negatively affects dynamic cyclic fatigue resistance. Dynamic cyclic resistance is not affected by the number of sterilization cycles.